Empowering youth sport environments: Implications for daily moderate-to-vigorous physical activity and adiposity - Sally A.M. Fenton; Joan L. Duda; Paul R. Appleton; Timothy G. Barrett (Elsevier, 2017)
Background: Evidence suggests involvement in youth sport does not guarantee daily guidelines for moderate-to-vigorous physical activity (MVPA) are met, and participation may not mitigate the risks associated with physical inactivity. The need to promote higher habitual MVPA engagement amongst children active in the youth sport context has therefore been underlined. Framed by self-determination theory, the aim of the present study was to examine the implications of the motivational climate created in youth sport, for children's daily engagement in MVPA and associated adiposity. Specifically, we sought to test a motivational sequence in which children's perceptions of an empowering coach-created motivational climate were related to autonomous and controlled motivation, which in turn predicted sport-related enjoyment. Finally, enjoyment was assumed to predict accelerometer assessed daily MVPA and, following this, adiposity. Methods: Male and female youth sport participants aged 9-16 years (n = 112) completed multi-section questionnaires assessing their perceptions of the motivational climate created in youth sport (i.e., autonomy supportive, task involving, socially supportive), autonomous and controlled motivation, and sport-related enjoyment. Daily MVPA engagement was determined via 7 days of accelerometry. Percent body fat (BF%) was estimated using bio-electrical impedance analysis. Results: Path analysis revealed perceptions of an empowering motivational climate positively predicted players' autonomous motivation, and in turn, sport-related enjoyment. Enjoyment was also significantly negatively related to players' BF%, via a positive association with daily MVPA. Conclusion: Fostering more empowering youth sport environments may hold implications for the prevention of excess adiposity, through encouraging higher habitual MVPA engagement. Findings may inform the optimal design of youth sport settings for MVPA promotion, and contribute towards associated healthy weight maintenance amongst youth active in this context. Longitudinal and intervention studies are required to confirm these results.